Situation Report: Poland, 1 April 1968 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Repressive Measures against Warsaw University Students The Stand of Religious Bodies Reaction to Czechoslovak Events Polish-Danish Trade Protocol East-West Contacts